2009
DOI: 10.1136/tc.2009.029736
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette brand preference as a function of price among smoking youths in Canada: are they smoking premium, discount or native brands?

Abstract: Discount and native cigarette brands are commonly used by a substantial number of smoking youths in Canada. Additional research is required to better understand the reasons behind different cigarette brand preferences and how youths are able to access premium, discount and illicit native cigarettes. Moreover, ongoing surveillance of the cigarette brand preferences of youths is required for guiding future tobacco control policy and programming activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…Other studies have found similar results. For example, a study for Canada showed that discount brands and native brands were more popular among youth smokers with relatively less spending money and higher cigarette consumption 28. Another study found that the use of discount cigarettes among adults from the USA was associated with lower household income and higher daily consumption 6.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found similar results. For example, a study for Canada showed that discount brands and native brands were more popular among youth smokers with relatively less spending money and higher cigarette consumption 28. Another study found that the use of discount cigarettes among adults from the USA was associated with lower household income and higher daily consumption 6.…”
Section: Discussionmentioning
confidence: 99%
“…These large discrepancies in Federal and Provincial/Territorial taxes are important as price sensitive youth may compensate for price/taxation increases by shifting from FM cigarettes to cheaper RYO cigarettes instead of quitting or reducing consumption [1]. For instance, recent research has identified that in the FM cigarette market, a substantial proportion of Canadian youth smokers now regularly smoke ‘discount’ cigarettes instead of more expensive premium cigarette brands [12]. As such, it would be informative to build on such evidence by examining the prevalence of RYO tobacco use among Canadian youth.…”
Section: Introductionmentioning
confidence: 99%
“…Self-report data from Canada’s annual Youth Smoking Survey have shown that 8% of Ontario high school students who currently smoke [31] and 22% of those who smoke daily [10] “usually” smoke “cigarettes from First Nations / Native brand cigarettes” (i.e., cigarettes meeting those studies’ definitions of contraband tobacco). Furthermore, students who usually smoke contraband cigarettes report significantly higher tobacco consumption rates than those smoking premium name brands [12]. Similar relationships have been observed for adult smokers: usual use of inexpensive tobacco (e.g.…”
Section: Introductionmentioning
confidence: 68%
“…These studies suggest contraband may be undermining tobacco control strategies aimed at preventing tobacco use among youth [4,8,10,12]. It is less clear, however, what impact contraband tobacco is having on young adults’ tobacco use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation